Urinary Bladder Weight and Function in a Rat Model of Mild Hyperglycemia and Its Treatment With Dapagliflozin - Yesilyurt, Zeynep Elif; Erdogan, Betül Rabia; Karaomerlioglu, Irem; Muderrisoglu, Ayhanim Elif; Michel, Martin Christian; Arioglu-Inan, Ebru (Frontiers in Pharmacology, 2019)
Hypertrophy and dysfunction of the urinary bladder are consistently observed in animal models of type 1 and less consistently in those of type 2 diabetes. We have tested the effects of mild hyperglycemia (n = 10 per group) in a randomized, blinded study and, in a blinded pilot study, of type 2 diabetes (n = 6 per group) and its treatment with dapagliflozin (1 mg/kg/day) on weight, contraction and relaxation of the rat bladder. Based on a combination of high-fat diet and a low dose of streptozotocin, animals in the main study reached a mean peak blood glucose level of about 300 mg/dl, which declined to 205 mg/dl at study end. This was associated with a small if any increase in bladder weight. In a pooled analysis of all animals of the main and the pilot study, we detected a correlation of moderate strength between blood glucose and bladder weight (r2 = 0.2013; P = 0.0003 for Pearson correlation coefficient). Neither the main nor the pilot study found evidence for an altered contractility (responses to carbachol or KCl) or relaxation (responses to isoprenaline, fenoterol, CL 316,243 or forskolin). Treatment with dapagliflozin in the absence of hyperglycemia increased diuresis in the main study by 43% relative to control and increased bladder weight by 15% in the pooled groups of both studies (post-hoc analysis). We conclude that mild hyperglycemia has no major effects on bladder hypertrophy or function.